Development of a novel Bruton’s tyrosine kinase inhibitor that exerts anti-cancer activities potentiates response of chemotherapeutic agents in multiple myeloma stem cell-like cells - Elbezanti, Weam Othman; Al-Odat, Omar S.; Chitren, Robert; Singh, Jaikee Kumar; Srivastava, Sandeep Kumar; Gowda, Krishne; Amin, Shantu; Robertson, Gavin P.; Nemmara, Venkatesh V.; Jonnalagadda, Subash C.; Budak-Alpdogan, Tulin; Pandey, Manoj K. (Frontiers in Pharmacology, 2022)
Despite recent improvements in multiple myeloma (MM) treatment, MM remains an incurable disease and most patients experience a relapse. The major reason for myeloma recurrence is the persistent stem cell-like population. It has been demonstrated that overexpression of Bruton’s tyrosine kinase (BTK) in MM stem cell-like cells is correlated with drug resistance and poor prognosis. We have developed a novel small BTK inhibitor, KS151, which is unique compared to other BTK inhibitors. Unlike ibrutinib, and the other BTK inhibitors such as acalabrutinib, orelabrutinib, and zanubrutinib that covalently bind to the C481 residue in the BTK kinase domain, KS151 can inhibit BTK activities without binding to C481. This feature of KS151 is important because C481 becomes mutated in many patients and causes drug resistance. We demonstrated that KS151 inhibits in vitro BTK kinase activities and is more potent than ibrutinib. Furthermore, by performing a semi-quantitative, sandwich-based array for 71-tyrosine kinase phosphorylation, we found that KS151 specifically inhibits BTK. Our western blotting data showed that KS151 inhibits BTK signaling pathways and is effective against bortezomib-resistant cells as well as MM stem cell-like cells. Moreover, KS151 potentiates the apoptotic response of bortezomib, lenalidomide, and panobinostat in both MM and stem cell-like cells. Interestingly, KS151 inhibits stemness markers and is efficient in inhibiting Nanog and Gli1 stemness markers even when MM cells were co-cultured with bone marrow stromal cells (BMSCs). Overall, our results show that we have developed a novel BTK inhibitor effective against the stem cell-like population, and potentiates the response of chemotherapeutic agents.